Promotion of NLRP3 autophagosome degradation by PV-K nanodevice for protection against macrophage pyroptosis-mediated lung injury - Yan Fan; Jian Mei; Yuehao Shen; Ying Gao; Lina Zhao; Shuqi Meng; Shuai Zhou; Yu Qian; Ying Zhang; Zhiwei Wang; Yu Song; Jianfeng Liu; et al. (Journal of Nanobiotechnology, 2025)
Abstract Acute respiratory distress syndrome (ARDS) has emerged as a significant global health challenge, with no definitive curative treatment available. Recent evidence suggests that pyroptosis of immune cells plays a pivotal role in the pathogenesis of ARDS. Targeting and modulating immune cell pyroptosis in lung tissue may offer a promising strategy to mitigate the harmful inflammation associated with this condition. In this study, we designed and synthesized a novel class of peptide-functionalized nanoparticles, PV-K, which possess an intrinsic capacity for phagocytosis by macrophages. Concurrently, the incorporation of two FFD functional groups into a single polypeptide enhances the biological activity of PV-K. Amazingly, PV-K demonstrated potent inhibitory effects on nucleotide-binding domain, leucine-rich repeat, and pyrin domain-containing protein 3 (NLRP3)-mediated pyroptosis in both mouse bone marrow-derived macrophages and the human THP-1 cell-derived macrophages. In both lipopolysaccharide and cecal ligation and puncture induced acute lung injury mouse models, treatment with PV-K significantly reduced disease severity by alleviating pulmonary inflammation and inhibiting macrophage pyroptosis. Transcriptomic analysis revealed that PV-K enhanced SQSM1/p62-mediated autophagy through upregulation of the NRF2 signaling pathway. Mechanistically, PV-K facilitated the interaction between SQSTM1/p62 and NLRP3, promoting the autolysosomal degradation of NLRP3. Notably, the inhibitory effect of PV-K on macrophage pyroptosis during acute lung injury was abrogated in Nrf2 -/- mice. This study introduces a novel nanotherapeutic approach aiming at regulating macrophage pyroptosis by facilitating NLRP3 degradation, thereby controlling inflammation in ARDS/ALI. This strategy may complement existing clinical treatments for ARDS/ALI.